2001
DOI: 10.1021/om000859p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Arylstannanes from Arylamines

Abstract: Arylamines have been converted into aryltrimethylammonium salts, which on reaction with sodium trimethylstannide (1) in liquid ammonia afford aryltrimethylstannanes by the S RN 1 mechanism. With (4-methoxyphenyl)-(2), (1-naphthyl)-(4), phenyl-(6), (4-acetylphenyl)-(8), and (4-cyanophenyl)trimethylammonium salts (10) the substitution products are obtained in good to excellent yields (45-100%). Also, the photostimulated reaction of (2-pyridyl)trimethylammonium iodide (12) with 1 leads to the substitution product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…As seen from Table 1, arylstannane 1 reacted with benzoyl-and naphtoyl chloride in 60 h rendering the diarylketones 10 [7] and 11 in good yields (65% and 60%, respectively) (entries 1 and 2). Similar reactions carried out with arylstannanes 2-4 proceeded efficiently giving diarylketones 12 (78%), 13 (68%), 14 (65%) and 15 (70%) [7] (entries [3][4][5][6]. It should be mentioned that the reaction conditions are mild enough to be applied to acid sensitive molecules such as 5, leading to the corresponding ketone 16 (40%, 20 h), the protecting group remaining unchanged (entry 7) [8].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…As seen from Table 1, arylstannane 1 reacted with benzoyl-and naphtoyl chloride in 60 h rendering the diarylketones 10 [7] and 11 in good yields (65% and 60%, respectively) (entries 1 and 2). Similar reactions carried out with arylstannanes 2-4 proceeded efficiently giving diarylketones 12 (78%), 13 (68%), 14 (65%) and 15 (70%) [7] (entries [3][4][5][6]. It should be mentioned that the reaction conditions are mild enough to be applied to acid sensitive molecules such as 5, leading to the corresponding ketone 16 (40%, 20 h), the protecting group remaining unchanged (entry 7) [8].…”
Section: Resultsmentioning
confidence: 96%
“…All acid chlorides were commercially available and used as received except benzoyl chloride which was fractionally distilled under nitrogen before use. The aryltins were prepared according to the literature methods [5,6]. Chlorobenzene was dried by standard methods, distilled under dry nitrogen and stored over molecular sieves.…”
Section: Methodsmentioning
confidence: 99%
“…Based on our experimental results and the related studies reported in literature, a SET mechanism is proposed (Scheme ). Thus, reaction of ArNMe 3 + I − with Ar 1 ZnCl forms [ArNMe 3 + I ‐ ] ⋅− via SET . The following action of [ArNMe 3 + I ‐ ] ⋅− with Ar 1 ZnCl gives [Ar−Ar 1 ] ⋅− and releases ZnICl and NMe 3 .…”
Section: Optimization Of the Reaction Conditions[a]mentioning
confidence: 99%
“…Me 3 SnAr can also be synthesized by the photoinduced reaction of aryldiethylphosphate esters [42] or aryltrimethylammonium salts [43] with Me 3 Sn À ions in liquid ammonia, in excellent yields (85-100%). These routes allow for the synthesis of arylstannanes in very good yields from inexpensive and commercially available phenols and anilines, which are easily converted to the corresponding phosphate esters and ammonium salts, respectively.…”
Section: Cyanide Ions As the Nucleophilementioning
confidence: 99%